2002
DOI: 10.1139/f02-127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pedigree analysis in natural populations of fishes: approaches, applications, and practical considerations

Abstract: Molecular markers can provide information on the family structure of natural fish populations through molecular pedigree analysis. This information, which is otherwise difficult to obtain, can give important insights into the expression and evolution of phenotypic traits. We review the literature to provide examples of how molecular pedigree analysis has been used extensively to examine patterns of distribution, dispersal, and social behaviour in fishes and how it provides a tool for the estimation of quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 93 publications
0
50
0
Order By: Relevance
“…Various authors have discussed the diverse reproductive behaviors and tactics found in fishes through genetic assessments of parentage (Taborsky, 2001(Taborsky, , 2008Wilson & Ferguson, 2002;Hain & Neff, 2007), and their findings have revolutionized the study of reproductive behavior, revealing that individuals of many species engage in extra-pair copulations, including parasitic spawning behavior between satellite and territorial males such as sneaking, egg piracy and female mimicry of cooperative breeding between satellite and territorial males.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have discussed the diverse reproductive behaviors and tactics found in fishes through genetic assessments of parentage (Taborsky, 2001(Taborsky, , 2008Wilson & Ferguson, 2002;Hain & Neff, 2007), and their findings have revolutionized the study of reproductive behavior, revealing that individuals of many species engage in extra-pair copulations, including parasitic spawning behavior between satellite and territorial males such as sneaking, egg piracy and female mimicry of cooperative breeding between satellite and territorial males.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attributed disappointing results in estimating heritability of body weight in Soay sheep to a lack of relatedness structure in the sample, as well as to insufficient amounts of genotypic information. Application to natural populations therefore requires careful consideration of biological processes such as social grouping (Ritland, 2000), as well as appropriate design of sampling strategy (Wilson & Ferguson, 2002), such that significant numbers of relatives are sampled. Since such structure can lead to bias and inaccuracy in the molecular pedigree analysis (discussed above), efficient estimation of genetic parameters in small, highly structured samples may require estimation of allele frequencies from a larger sample more representative of the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the thirty microsatellite loci, only one (P04) is from a congeneric species, P. pelagicus, while eight (E9, E11, E13, E17, E18, E20, E24, and E28) from EST sequences, three (PN22, PN24, and PN27) from GenBank data and eighteen (locus named 'C' and 'H' series) from the enriched genomic library. Genomic DNA was extracted from crab pleopods using a modified CTAB extraction protocol (Wilson 1987) and resuspended at 5-10 ng/ll. PCR was performed in a total of 20 ll reaction mixture containing 1 9 PCR buffer (promega), 2.5 lmol MgCl 2 , 100 lmol each dNTP, 0.5 lmol of each primer, 0.5 U Taq DNA polymerase (promega), and approximately 10 ng template DNA.…”
mentioning
confidence: 99%